Introduction to clinical neurology - Gelb, Douglas James, 1957- ([New York] : Oxford University Press, 2016)
Offering a clear picture of neurology, this text is organised in the same way students learn neurology during their training, beginning with the initial neurologic exam and modifications on the exam to interpretation of the exam and problem solving. This edition features the latest drugs and treamtents.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 16, 2016).
Keywords: Neurology